2015
DOI: 10.1136/archdischild-2014-307272
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory control and supplemental oxygen in premature infants with apparent chronic lung disease

Abstract: Objectives Our goal was to evaluate changes in respiratory pattern among premature infants born at less than 29 weeks gestation who underwent a physiologic challenge at 36 weeks post-menstrual age with systematic reductions in supplemental oxygen and inspired airflow. Study Design Subjects were all infants enrolled in the Prematurity and Respiratory Outcomes Program at St. Louis Children’s Hospital and eligible for a physiologic challenge protocol because they were receiving supplemental oxygen or augmented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…These “mismatches” between BPD and later outcomes may be due to a variety of factors related to the heterogeneity of lung disease in ELGAN, the socioeconomic factors that influence symptomatic respiratory disease in infancy, and the inherent limitations in using supplemental oxygen alone as a marker for lung disease (8, 16). For instance, the use of high-flow nasal cannula (without supplemental oxygen) as an alternative to positive airway pressure, and the application of supplemental oxygen to mitigate the effects of dysmature respiratory control, may result in misclassification of BPD (16, 34). Interestingly, although the addition of BPD and other 36-week variables did not substantially alter the specific perinatal variables selected for 36-week models, the effects of gestational age, male sex, intrauterine growth restriction and parental history of asthma decreased in the 36-week PRD model, but the effect of Black race increased.…”
Section: Discussionmentioning
confidence: 99%
“…These “mismatches” between BPD and later outcomes may be due to a variety of factors related to the heterogeneity of lung disease in ELGAN, the socioeconomic factors that influence symptomatic respiratory disease in infancy, and the inherent limitations in using supplemental oxygen alone as a marker for lung disease (8, 16). For instance, the use of high-flow nasal cannula (without supplemental oxygen) as an alternative to positive airway pressure, and the application of supplemental oxygen to mitigate the effects of dysmature respiratory control, may result in misclassification of BPD (16, 34). Interestingly, although the addition of BPD and other 36-week variables did not substantially alter the specific perinatal variables selected for 36-week models, the effects of gestational age, male sex, intrauterine growth restriction and parental history of asthma decreased in the 36-week PRD model, but the effect of Black race increased.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our study is that our cohorts did not include premature infants on mechanical support beyond NICU discharge; however, these babies would likely be included in this new category given that this group was characterized by prolonged mechanical ventilatory support (mean 59 days). Given their exceedingly high risk for severe complications, we believe these vulnerable infants with "very severe BPD" (new level IV) may require a detailed assessment of their upper and large airways 28 , lung parenchyma structure [12][13][14][15][16] , pulmonary vasculature 29 , and ventilatory responses 30,31 , as well as intense surveillance by a specialized multi-disciplinary team during and after NICU discharge 32 . We feel that babies with ≥120 days of O2 requirements should be considered in a different severity category because we found they have a much greater risk of respiratory complications (see Table 3) and may require new strategies to improve their outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of these receptors allows for an immediate and rapid rise in ventilation to compensate for hypoxemia . Abnormal ventilatory responses to hypoxic and hypercarbic challenges have been reported in animal models as well as in children and adults with a history of BPD . These changes in respiratory control are interconnected with abnormal carotid body development secondary to chronic hypoxemia or hyperoxia .…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Abnormal ventilatory responses to hypoxic and hypercarbic challenges have been reported in animal models as well as in children and adults with a history of BPD. 21,[39][40][41][42][43][44] These changes in respiratory control are interconnected with abnormal carotid body development secondary to chronic hypoxemia or hyperoxia. 10,20,29,40,42,[45][46][47] Animal models have also shown that these changes are long lasting and thus may increase the risk of SDB in this vulnerable population.…”
mentioning
confidence: 99%